(untitled) (Bangladesh Journal of Plant Breeding and Genetics, 2015)
Ten okra genotypes were evaluated at the Teaching and Research Farm, University of Maiduguri, Nigeria, during 2015 and 2016 dry seasons. The objective was to assess the degree of genetic diversity and heritability of different traits of okra. The combined analysis of variance revealed highly significant (p<0.01) differences among okra genotypes for plant height, days to 50% flowering, fresh pod length, fresh pod diameter and fresh weight per pod in both years. High heritability, genetic advance as percent of the mean and genotypic coefficient of variation were observed for all the studied characters except fresh pod diameter and days to 50% flowering. This indicated diverse genetic background and predominance of additive gene control for these characters, thereby providing a great scope for selection. Mahanalobis D2 analysis allocated the 10 genotypes into four clusters. Cluster I was the highest cluster consisting four genotypes, followed by cluster II with three genotypes and cluster III two genotypes, while cluster IV was monogenotypic. Involvement of the highest yielding genotypes (Salkade, Yar gagure and Kwadag) in hybridization could increase novel recombinants to exploit transgressive segregates with high genetic yield potentials.